THE STUDENTS’ RESPONSE OF INTANGIBLE REWARDS IN MOTIVATING STUDENTS TO LEARN ENGLISH - Putri Damayanti; St. Asriati AM; Eka Prabawati Rum (English Language Teaching Methodology, 2021)
Intangible Reward refers to a class of rewards which have no material or monetary value but can keep the employee feeling recognized and motivated (Kharel, 2012). The objective of this research were to describe the types of intangible rewards were given by the teacher in motivating students and to describe the students’ responses to the intangible reward in motivating students. The method of this research was descriptive qualitative method. The subject of this research was the eight grade of SMP Muhammadiyah 12 makassar. The sample of this research was class A that consisted of 20 students. The researcher also interviewed the teacher to gain more information about the effect of intangible rewards for students. The researcher used observation checklist and interview as instrument of collecting the data. Technique of data analysis consisted of data reduction, data display, and drawing conclusion /verification. The findings of the research showed that there were two types of rewards used by the teachers motivating students in learning English at the eight grade of SMP Muhammadiyah 12 Makassar. They were; praise/verbal reinforcement and written praise. Verbal praise consisted of good job, i like it, nice, excellent, very good, and written praise consisted of teacher gave grade,mark and positive comment on student’s sheet. The researcher found that intangible rewards gave the positive effects for the students that were; reward created the class more interesting, increased the positive behavior or expected behavior of students in the classroom, made students feel happy and more active participate in class, it can increase the feeling of competition among students in the classroom, and it can encourage the students in completed their task and homework.